OPTIMALISASI PENGAWASAN BUNKER BAHAN BAKAR KAPAL TNI-AL UNTUK MENGURANGI TERJADINYA OIL SPIL DI DERMAGA KOARMADA OLEH PT. PERTAMINA TRANS KONTINENTAL CABANG SURABAYA - Andy Wahyu Hermanto; Jevri Eko Satria (Dinamika Bahari, 2019)
ABSTRACT Refueling activities (bunkers) is a filling activity fuel is done routinely before the ship is ready to sail, but in tandem Over time the bunker activity also brought new problems such as the oil incident spill that occurs at the Koarmada pier. Potential problems that occur causing the oil spill to be very high. The objectives of this study are 1). For find out about bunker surveillance activities at the Koarmada pier, 2). Knowing the factors that cause oil spills and 3). The efforts made by PT. Pertamina Trans Continental Surabaya branch to reduce the occurrence of oil spills. The research method used is 1). Descriptive qualitative by describing in detail the implementation of bunker supervision at the Koarmada pier. Collection Data is done by interview, observation, literature study and documentation in the form of photographs of the implementation of bunker supervision. From the results of the study it can be seen that 1). Supervision activities at the Koarmada pier are still not optimal. 2). Factors which are causing oil spills include education factors, knowledge factors, and factors equipment that is not feasible. Based on the research results, PT. Pertamina Trans Continental does 3). Efforts to reduce the occurrence of oil spills with more pay attention to the educational background in recruiting bunker workers, giving training and outreach to the supervisory team, giving strict sanctions to bunker workers if the bunker is implemented not according to procedures, update bunker equipment that is not feasible to use, do a thorough supervision, and do good communication and coordination and cooperation in supervision bunker activity